Effects of different feed items on the growth and survival of endangered riverine catfish Rita rita (Hamilton) - Amin, MR; Mollah, MFA; Ali, MR; Nahiduzzaman, M (University Journal of Zoology, Rajshahi University, 2010)
The study was conducted to determine a suitable feed for the desirable growth of riverine catfish Rita rita (Hamilton) from January 2006 to December 2006. The experiment had three treatments with three replicates. Nine chambers of the raceway each of size 1.83 × 1.12 sq meter were used. Local prawn, chicken viscera and commercially available formulated feed (CP) were supplied in treatment T1, T2 and T3, respectively at the rate of 7% body weight. Feed was supplied twice in a day in the early morning and in the evening as the fish is nocturnal. The initial average weight of fish was 24.93±0.05g, 24.99±0.04g and 24.95±0.04g in T1, T2 and T3, respectively. The final weight of the fish under three treatments was 425.05±1.04g, 425.68±1.05g and 177.61±1.45g respectively. The initial length was 8.48±0.02, 8.49±0.02 and 8.50±0.01 in T1, T2 and T3, respectively. The final length was 25.22±0.06 cm, 25.21±0.14 cm and 14.87±0.13 cm in T1, T2 and T3, respectively. The mean final weight and length was significantly (p<0.05) higher in T1 and T2 compared with T3. However, there was no significant difference (p>0.05) between T1 and T2 in terms of final weight and length was concerned. Better growth performances, however, were observed in T2 and T1, where prawn and chicken viscera were supplied as feed respectively. Lowest growth performance was observed in T3 where formulated feed (CP feed) was supplied. Key Words: Riverine Catfish; Feed; Growth; SGR; Survival. DOI: 10.3329/ujzru.v28i0.5279 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 11-14